REDUCING THE TECHNICAL ERRORS OF THE STUDENTS TO THE RECEIVING THE BALL WITH TWO HANDS FROM SERVE PROCEDURE - Constantin Ciorbă; Virgil Larionescu Moroşan (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
One of the most difficult problems confronted by specialists in this area of study is preventing and correcting technical mistakes of the students, as future teachers. This work approaches the problem in an innovative manner, i.e. by using support devices, which are designed to reduce not only the time requested for acquiring the kinesthetic skills and proficiency, but also to generate new exercise structures intended to continually reduce technical mistakes. By applying the auxiliary device "volleyball bangle", we were able to reduce by about 30% technical errors in the execution of "receiving the ball with two hands from serve " procedure, in the game of volleyball.